Expresión de SURVIVINA, BCL-XL, STAT3 y STAT5 en el pronóstico de pacientes con leucemia aguda - García Téllez, Génesis (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
Acute leukemia is the malignant clonal proliferation of immature hematopoietic cells of the blast type that can affect bone marrow (BM) or peripheral blood (SP), it is classified as myeloid (AML) and lymphoid (ALL). Leukemia prognosis is determined according to the following parameters: age, sex, number of blast cells, outcome of minimal residual disease, and molecular and chromosomal abnormalities. Despite this, it has been observed that many patients with a similar prognosis respond differently to treatment. The signal transducing and activating proteins of transcription 3 and 5, and the antiapoptotic proteins BCL-XL and SURVIVIN participate in mechanisms of proliferation and inhibition of apoptosis; In addition, they have been associated with resistance to chemotherapy. Objective. Determine the expression of STAT3, STAT5 BCL-xL (BCL2L1) and SURVIVIN (BIRC5) in patients with acute leukemia and its association with the prognosis of the disease. Materials and methods. Bone marrow and/or peripheral blood samples were taken from pediatric and adult patients diagnosed with de novo leukemia, and the expression of STAT3?, STAT3?, STAT5A, STAT5B, BCL2L1, and BIRC5 was analyzed by RT-qPCR. Results. A total of 71 cases of de novo acute leukemia were obtained. The difference between gene expression was statistically significant in the following cases: pediatric patients with B-ALL, STAT3? and STAT3? were under expressed and BIRC5 was overexpressed; in adult patients with B-ALL, STAT3? was under expressed and BIRC5 was overexpressed, and in adults with AML, STAT3?, STAT3?, STAT5A, and BIRC5 were overexpressed. STAT3? STAT3?, STAT5A, and the STAT5B/A ratio were associated with risk by age in pediatric ALL patients. The risk by leukocyte count was associated with the STAT5B/A index in pediatric ALL. Statistically significant positive correlations between gene expression were found in most pediatric and adult patients.

La leucemia aguda es la proliferación clonal maligna de células hematopoyéticas inmaduras de tipo blástico que pueden afectar médula ósea (MO) o sangre periférica (SP), esta se clasifica en mieloide (LMA) y linfoide (LLA). El pronóstico de la leucemia se determina de acuerdo con los siguientes parámetros: edad, sexo, cantidad de blastos, resultado de la enfermedad residual medible y anormalidades moleculares y cromosómicas. A pesar de ello, se ha observado que muchos pacientes con pronóstico semejante responden diferente al tratamiento. Las proteínas transductoras de señales y activadoras de la transcripción 3 y 5, y las proteínas antiapoptóticas Bcl-xL y survivina participan en mecanismos de proliferación e inhibición de la apoptosis; además, se les ha relacionado con resistencia a la quimioterapia. Objetivo general. Determinar la expresión de STAT3, STAT5 BCL-xL (BCL2L1) y SURVIVINA (BIRC5) en pacientes con leucemia aguda y su asociación con el pronóstico de la enfermedad. Materiales y métodos. A pacientes pediátricos y adultos con diagnóstico de leucemia de novo se les tomó muestra de médula ósea y/o sangre periférica, se analizó la expresión de STAT3?, STAT3?, STAT5A, STAT5B, BCL2L1 y BIRC5 mediante RT-qPCR. Resultados. Se obtuvieron 71 casos de leucemia aguda de novo. La diferencia entre la expresión de genes fue estadísticamente significativa en los siguientes casos: pacientes pediátricos con LLA-B, STAT3? y STAT3? se sub-expresó y BIRC5 se sobre-expresó; en los pacientes adultos con LLA-B, se sub-expresó STAT3? y se sobreexpresó BIRC5 y en adultos con LMA se sobreexpresaron STAT3? STAT3?, STAT5A y BIRC5. STAT3? STAT3?, STAT5A y la relación STAT5B/A se asociaron al riesgo por edad en pacientes LLA pediátricos. El riesgo por conteo de leucocitos se asoció a la relación de STAT5B/A en LLA pediátricos. En la mayoría de los pacientes pediátricos y adultos se encontraron correlaciones positivas estadísticamente significativas entre la expresión de genes.
Facultad de Ciencias Médicas y Biológicas. Maestría en Ciencias de la Salud
Keywords: info:eu-repo/classification/cti/3; FCMB-R-M-2023-1138; Factor pronóstico; Sobreexpresión; Supervivencia; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16701